Effect of the oil‐paper insulation aging on partial discharge characteristics in a hemispherical surface model. Issue 5 (1st July 2019) - Wang, Yongqiang; Zhang, Xia; Jiang, Xiaolei; Wang, Yunjia
Abstract : To investigate the effect of aging on surface discharge of the pressboard on the shielding electrode at the end of bushing, a thermal aging preparation methods of different aging degrees of pressboard samples, surface defect model, and the associated hemisphere are designed and the step‐up method is used for subsequent experimental work. Finally, the partial discharges (PDs) under different degrees of aging are compared and combined with Fourier Transform Infrared spectra and electric field simulation. Results show that the pre‐discharge occurs mainly in the oil gap between the hemispherical electrode edge and the pressboard. The aging of the pressboard exerts no obvious effect on the discharge characteristics in the initial stage of PD; with the development of the discharge, the development of aging of pressboard leads to a higher electric field intensity acting over a greater area, the more intense the discharge, the faster the relative discharge increases and the larger its amplitude. This discharge will cause decomposition of the oil in the pores of the aging pressboard thus generating gas bubbles which will move as discharge develops. When the bubbles reach the surface of the pressboard, the local electric field intensity will increase and the discharge will become more intense.